Dynamic Status of SII and SIRI Alters the Risk of Cardiovascular Diseases: Evidence from Kailuan Cohort Study - Li, Jun; He, Di; Yu, Jiazhou; Chen, Shuohua; Wu, Qiong; Cheng, Zongxue; Wei, Qiaohui; Xu, Yuying; Zhu, Yimin; Wu, Shouling (Journal of inflammation research, 2022)
Background: Two novel systemic inflammation indices, SII and SIRI, are associated with increased risk of cardiovascular diseases (CVD). However, SII and SIRI are prone to change over time and the association between changeable status and long-term outcome risk remains to be uncovered. This study aims to examine the association between the dynamic status of SII and SIRI and risk of CVD. Methods: This prospective study included a total of 45,809 subjects without MI, stroke and cancer prior to or in 2010 (baseline of this study). The dynamic status of SII and SIRI during 2006, 2008, and 2010 was assessed by dynamic trajectories (primary exposure), annual increase, and average value. The outcome was CVD incidence during 8.6 years' follow-up. Multiple Cox regression models were used to calculate the adjusted hazard ratios (HRs) and confidence intervals (95% CIs). Results: Four dynamic trajectories of SII and SIRI were identified as follows: low stable pattern, moderate stable pattern, increase pattern, and decrease pattern. For SII, compared with "low stable pattern", after controlling confounders and level of SII in 2006, adjusted HRs were 1.24 (95% CI = 1.02-1.51) for "increase pattern" and 1.11 (95% CI = 1.00-1.23) for "moderate-stable pattern" while the association was not significant for "decrease pattern". Additionally, the highest group of annual SII increase and average SII had respective HR of 1.20 (95% CI = 1.05-1.37) and 1.32 (95% CI = 1.13-1.55). The results were consistent for SIRI. "Increase pattern" and "moderate stable pattern" increased the risk of CVD by 38% (HR = 1.38, 95% CI = 1.17-1.63) and 12% (HR = 1.12, 95% CI = 1.01-1.25), while no significant association was found for "decrease pattern". The highest group of annual SIRI increase and average SIRI had respective HR of 1.25 (95% CI = 1.09-1.44) and 1.39 (95% CI = 1.19-1.63). Conclusion: Dynamic status of SII and SIRI was significantly associated with risk of CVD, which highlighted that we should focus on the dynamic change of SII and SIRI. Keywords: systemic inflammation, dynamic status, prospective study, cardiovascular diseases